OVERVIEW OF SELF-ESTEEM AMONG STUDENTS AT MAN 1 TASIKMALAYA - Muhammad Ramdani Alfain; Feida Noorlaila Isti'adah; Anandha Putri Rahimsyah (Jurnal Kajian Pendidikan dan Psikologi, 2024)
The purpose of this study was to describe the condition of self-esteem of grade X students of MAN 1 Tasikmalaya. This research is descriptive quantitative research with a sample size of 438 students from a population of 500 students. The sampling technique used incidental and used the Tafarodi & Swann (2001) instrument adopted by Wulandari, W (2020). In this study, it was revealed that the condition of self-esteem of class X students of MAN 1 Tasikmalaya was generally in the moderate category or if it was presented was 415 students (95%), which means that most students already have good self-esteem but have not fully shown high self-esteem as shown by students with high self-esteem. Therefore, better improvement is needed so that high self-esteem can be achieved as much as possible. There is no significant difference between male and female students in the level of self-esteem between male and female students because one of the factors that affect self-esteem is the environment. Where they have the same environment, be it at school or boarding school, the same business and activities. Therefore, there is a need for guidance and counselling services using classical guidance. Classical guidance is an efficient service, especially in dealing with the problem of the ratio of the number of counsellors and clients.